# |
ODE |
Mathematica |
Maple |
\[
{}y = \left (y \,{\mathrm e}^{y}-2 x \right ) y^{\prime }
\] |
✓ |
✓ |
|
\[
{}\cos \left (x \right ) y^{\prime }+y \sin \left (x \right ) = 1
\] |
✓ |
✓ |
|
\[
{}\cos \left (x \right )^{2} \sin \left (x \right ) y^{\prime }+y \cos \left (x \right )^{3} = 1
\] |
✓ |
✓ |
|
\[
{}\left (1+x \right ) y^{\prime }+\left (x +2\right ) y = 2 x \,{\mathrm e}^{-x}
\] |
✓ |
✓ |
|
\[
{}\left (x +2\right )^{2} y^{\prime } = 5-8 y-4 x y
\] |
✓ |
✓ |
|
\[
{}r^{\prime }+r \sec \left (t \right ) = \cos \left (t \right )
\] |
✓ |
✓ |
|
\[
{}p^{\prime }+2 t p = p+4 t -2
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+\left (1+3 x \right ) y = {\mathrm e}^{-3 x}
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}-1\right ) y^{\prime }+2 y = \left (1+x \right )^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x +5 y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 2 x -3 y
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+y = {\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}y y^{\prime }-x = 2 y^{2}
\] |
✓ |
✓ |
|
\[
{}L i^{\prime }+R i = E
\] |
✓ |
✓ |
|
\[
{}T^{\prime } = k \left (T-T_{m} \right )
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+y = 4 x +1
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+4 x y = x^{3} {\mathrm e}^{x^{2}}
\] |
✓ |
✓ |
|
\[
{}\left (1+x \right ) y^{\prime }+y = \ln \left (x \right )
\] |
✓ |
✓ |
|
\[
{}x \left (1+x \right ) y^{\prime }+x y = 1
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-y \sin \left (x \right ) = 2 \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y \tan \left (x \right ) = \cos \left (x \right )^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 y = \left \{\begin {array}{cc} 1 & 0\le x \le 3 \\ 0 & 3<x \end {array}\right .
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = \left \{\begin {array}{cc} 1 & 0\le x \le 1 \\ -1 & 1<x \end {array}\right .
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 x y = \left \{\begin {array}{cc} x & 0\le x <1 \\ 0 & 1\le x \end {array}\right .
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime }+2 x y = \left \{\begin {array}{cc} x & 0\le x <1 \\ -x & 1\le x \end {array}\right .
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\left (\left \{\begin {array}{cc} 2 & 0\le x \le 1 \\ -\frac {2}{x} & 1<x \end {array}\right .\right ) y = 4 x
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\left (\left \{\begin {array}{cc} 1 & 0\le x \le 2 \\ 5 & 2<x \end {array}\right .\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-2 x y = 1
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-2 x y = -1
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y \,{\mathrm e}^{x} = 1
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime }-y = x^{3}
\] |
✓ |
✓ |
|
\[
{}x^{3} y^{\prime }+2 x^{2} y = 10 \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-\sin \left (x^{2}\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}1 = \left (y^{2}+x \right ) y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y+\left (2 x +x y-3\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }-4 y = x^{6} {\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }-4 y = x^{6} {\mathrm e}^{x}
\] |
✗ |
✗ |
|
\[
{}x y^{\prime }-4 y = x^{6} {\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}e^{\prime } = -\frac {e}{r c}
\] |
✓ |
✓ |
|
\[
{}2 x -1+\left (3 y+7\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {26 y}{5} = \frac {97 \sin \left (2 t \right )}{5}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-6 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x^{2}}{y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x^{2}}{y \left (x^{3}+1\right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = \sqrt {1-y^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x^{2}}{1+y^{2}}
\] |
✓ |
✓ |
|
\[
{}x y y^{\prime } = \sqrt {1+y^{2}}
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}-1\right ) y^{\prime }+2 x y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 3 y^{{2}/{3}}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+y = y^{2}
\] |
✓ |
✓ |
|
\[
{}2 x^{2} y y^{\prime }+y^{2} = 2
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-x y^{2} = 2 x y
\] |
✓ |
✓ |
|
\[
{}\left (1+z^{\prime }\right ) {\mathrm e}^{-z} = 1
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {3 x^{2}+4 x +2}{2 y-2}
\] |
✓ |
✓ |
|
\[
{}{\mathrm e}^{x}-\left (1+{\mathrm e}^{x}\right ) y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\frac {y}{x -1}+\frac {x y^{\prime }}{1+y} = 0
\] |
✓ |
✓ |
|
\[
{}x +2 x^{3}+\left (2 y^{3}+y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\frac {1}{\sqrt {x}}+\frac {y^{\prime }}{\sqrt {y}} = 0
\] |
✓ |
✓ |
|
\[
{}\frac {1}{\sqrt {-x^{2}+1}}+\frac {y^{\prime }}{\sqrt {1-y^{2}}} = 0
\] |
✓ |
✓ |
|
\[
{}2 x \sqrt {1-y^{2}}+y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \left (y-1\right ) \left (1+x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = {\mathrm e}^{x -y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {\sqrt {y}}{\sqrt {x}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {\sqrt {y}}{x}
\] |
✓ |
✓ |
|
\[
{}z^{\prime } = 10^{x +z}
\] |
✓ |
✓ |
|
\[
{}x^{\prime }+t = 1
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \cos \left (x -y\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-y = 2 x -3
\] |
✓ |
✓ |
|
\[
{}\left (x +2 y\right ) y^{\prime } = 1
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = 2 x +1
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \cos \left (-y+x -1\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\sin \left (x +y\right )^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 2 \sqrt {2 x +y+1}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \left (x +y+1\right )^{2}
\] |
✓ |
✓ |
|
\[
{}y^{2}+x y^{2}+\left (x^{2}-x^{2} y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\left (1+y^{2}\right ) \left ({\mathrm e}^{2 x}-{\mathrm e}^{y} y^{\prime }\right )-\left (1+y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x -y+\left (x +y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y-2 x y+x^{2} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 x y^{\prime } = y \left (2 x^{2}-y^{2}\right )
\] |
✓ |
✓ |
|
\[
{}y^{2}+x^{2} y^{\prime } = x y y^{\prime }
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+y^{2}\right ) y^{\prime } = 2 x y
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }-y = x \tan \left (\frac {y}{x}\right )
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = y-x \,{\mathrm e}^{\frac {y}{x}}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }-y = \left (x +y\right ) \ln \left (\frac {x +y}{x}\right )
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = y \cos \left (\frac {y}{x}\right )
\] |
✓ |
✓ |
|
\[
{}y+\sqrt {x y}-x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }-\sqrt {x^{2}-y^{2}}-y = 0
\] |
✓ |
✓ |
|
\[
{}x +y-\left (x -y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{2}+2 x y-y^{2}+\left (y^{2}+2 x y-x^{2}\right ) y^{\prime } = 0
\] |
✗ |
✓ |
|
\[
{}x y^{\prime }-y = y y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y^{2}+\left (x^{2}-x y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{2}+x y+x^{2} = x^{2} y^{\prime }
\] |
✓ |
✓ |
|
\[
{}\frac {1}{x^{2}-x y+y^{2}} = \frac {y^{\prime }}{2 y^{2}-x y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {2 x y}{3 x^{2}-y^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x}{y}+\frac {y}{x}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = y+\sqrt {y^{2}-x^{2}}
\] |
✓ |
✓ |
|
\[
{}y+\left (2 \sqrt {x y}-x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = y \ln \left (\frac {y}{x}\right )
\] |
✓ |
✓ |
|